Successful Management of Rhegmatogenous Retinal Detachment with Concomitant Cataract Using Combined Phacoemulsification, Pars Plana Vitrectomy, and Scleral Buckling: A Case Report - Ramzi Amin; Alfin Radhian (HM Publisher, 2024)
Rhegmatogenous retinal detachment (RRD) coexisting with significant cataract presents a complex surgical challenge, often necessitating combined phacoemulsification, pars plana vitrectomy (PPV), and potentially scleral buckling (SB) for optimal anatomical and visual outcomes. This report details the successful management of such a case using a combined surgical approach. A 43-year-old female presented with a one-week history of a sudden-onset black shadow in the nasal visual field of her right eye (OD), preceded by photopsia for one month. Visual acuity was 1/60 OD and 1/60 OS, non-improving with pinhole. Ophthalmic examination revealed an RRD with a superior retinal tear between the 1-2 o'clock position in the OD, associated undulation, and retinal folds. Bilateral immature senile cataracts (Nuclear Opalescence Grade 2, Nuclear Color Grade 2) were also noted. The patient underwent combined phacoemulsification with intraocular lens (IOL) implantation, 360° SB, 23-gauge PPV, endolaser photocoagulation around the break, and silicone oil tamponade in the OD. Postoperatively, the retina remained attached under silicone oil. Visual acuity improved to 6/21 OD at the 8-day follow-up. Postoperative intraocular pressure (IOP) elevation (39.4 mmHg OD) was managed medically. In conclusion, combined phacoemulsification, PPV, and SB proved effective in achieving both retinal reattachment and significant visual improvement in this patient with RRD and concomitant cataract. Careful surgical planning and postoperative management, including IOP control, are crucial for successful outcomes in these complex cases.